Nigeria: A Prime Example of the Resource Curse? Revisiting the Oil-Violence Link in the Niger Delta - Annegret Mähler (German Institute of Global and Area Studies (GIGA), 2010)
This paper studies the oil-violence link in the Niger Delta, systematically taking into consideration domestic and international contextual factors. The case study, which focuses on explaining the increase in violence since the second half of the 1990s, confirms the differentiated interplay of resource-specific and non-resource-specific causal factors. With regard to the key contextual conditions responsible for violence, the results underline the basic relevance of cultural cleavages and political-institutional and socioeconomic weakness that existed even before the beginning of the 'oil era'. Oil has indirectly boosted the risk of violent conflicts through a further distortion of the national economy. Moreover, the transition to democratic rule in 1999 decisively increased the opportunities for violent struggle, in a twofold manner: firstly, through the easing of political repression and, secondly, through the spread of armed youth groups, which have been fostered by corrupt politicians. These incidents imply that violence in the Niger Delta is increasingly driven by the autonomous dynamics of an economy of violence: the involvement of security forces, politicians and (international) businessmen in illegal oil theft helps to explain the perpetuation of the violent conflicts at a low level of intensity. – – Nigeria: ein 'Musterbeispiel' des Ressourcenfluchs? Eine kritische Evaluation des Zusammenhangs von Erdöl und Gewalt im Nigerdelta. Dieser Beitrag analysiert den Zusammenhang von Erdöl und Gewalt im Niger Delta unter systematischer Berücksichtigung von innerstaatlichen und internationalen Kontextfaktoren. Durch die Fallstudie, deren Schwerpunkt auf der Erklärung des Anstiegs der Gewalt seit der zweiten Hälfte der 1990er Jahre liegt, wird ein differenziertes Zusammenspiel von ressourcenspezifischen und nicht-ressourcenspezifischen Erklärungsvariablen untermauert. Die Befunde ergeben erstens, dass zentrale Kontextbedingungen, die zur Gewalt geführt haben - kulturelle Cleavages politisch-institutionelle sowie sozioökonomische Defizite - bereits vor Beginn der Erdölförderung in Nigeria virulent waren. Erdöl hat das Risiko gewaltsamer Konflikte zweitens durch eine tiefgreifende Verzerrung der Wirtschaftsstruktur indirekt weiter erhöht. Darüber hinaus hat drittens der Übergang zur Demokratie (1999) die Gewaltmöglichkeiten in zweifacher Hinsicht erhöht: auf der einen Seite durch ein Nachlassen politischer Repression, auf der anderen Seite durch die Ausbreitung bewaffneter Gruppierungen, die zunächst von korrupten Politikern herangezogen worden sind. Letzteres hat zur Folge, dass die Gewalt im Nigerdelta verstärkt den Dynamiken einer Ökonomie der Gewalt gehorcht: Dabei trägt die Beteiligung von Sicherheitskräften, Politikern und (internationalen) Geschäftsleuten an illegalem Ölhandel dazu bei die Perpetuierung gewaltsamer Konflikte auf niedrigem Gewaltniveau zu erklären.
Keywords: 300; Nigeria; natural resources; oil; political economy; violence; context sensitivity; Erdölvorkommen; Politische Gewalt; Sozialer Konflikt; Nigeria